Chemical fingerprint and simultaneous determination of alkaloids and flavonoids in aerial parts of genus Peganum indigenous to China based on HPLC‐UV: application of analysis on secondary metabolites accumulation. (29th May 2014) - Wen, Fangfang; Cheng, Xuemei; Liu, Wei; Xuan, Min; Zhang, Lei; Zhao, Xin; Shan, Meng; Li, Yan; Teng, Liang; Wang, Zhengtao; Wang, Changhong
ABSTRACT The aerial parts of genus Peganum are officially used in traditional Chinese medicine. The paper aims to establish a high‐performance liquid chromatography (HPLC) method for fingerprint analysis and simultaneous determination of three alkaloids and two flavonoids in aerial parts of genus Peganum, and to analyze accumulative difference of secondary metabolites in inter‐species, individuals of plants, inter‐/intra‐population and from different growing seasons. HPLC analysis was performed on a C18 column with gradient elution using 0.1% trifloroacetic acid and acetonitrile as mobile phase and detected at 265 nm, by conventional methodology validation. For fingerprint analysis, the RSDs of relative retention time and relative peak area of the characteristic peaks were within 0.07–0.78 and 0.94–9.09%, respectively. For simultaneous determination of vasicine, harmaline, harmine, deacetylpeganetin and peganetin, all calibration curves showed good linearity (r > 0.9990) within the test range. The relative standard deviations of precision, repeatability and stability test did not exceed 2.37, 2.68 and 2.67%, respectively. The average recoveries for the five analytes were between 96.47 and 101.20%. HPLC fingerprints play a minor role in authenticating and differentiating the herbs of different species of genus Peganum. However, the secondary metabolites levels of alkaloids and flavonoids in aerial parts of genus Peganum rely on species‐, habitat‐, and growth season‐dependent accumulation. Copyright © 2014 John Wiley & Sons, Ltd.